Nilai-Nilai Islam dalam Serat Wirid Hidayat Jati Karya Raden Ngabehi Ranggawarsita - Muhammad Ilham Aziz (Qurthuba: The Journal of History and Islamic Civilization, 2021)
Abstract: This article discussed the Islamic values within Serat Hidayat Jati written by Raden Ngabehi Ranggawarsita. Related to that issue, it also explored the condition of the Surakarta government (1802-1873) during the life of the author. The study methodologically used a historical method, which includes heuristics, verification, interpretation, and historiography. It approached the problems by employing the theory of hegemony with theoretical support from cognitive anthropology and semiotics. This study found that the Surakarta court had internal and external problems in 1802-1878 and a poet had an important role. Ranggwarsita was a closing poet of the Surakarta court who died on December 24, 1873. He was buried in Palar Village, Surakarta area. One of his works was Serat Wirid Hidayat Jati which contained Islamic values ​​such as monotheism and Sufism. From the value of faith (monotheism) can be seen from the pronunciation of la ilaha illallah which means there is no god but Allah. While the value of morality (Sufism) can be seen from the praise of dhikr to God. Keywords: Ranggawarsita, Wirid Hidyat Jati, Islamic values